Estrategias innovadoras en la comprensión lectora para el mejoramiento del rendimiento escolar en los niños y niñas del cuarto año de Educación Básica de la Unidad Educativa "Dr. Néstor Mogollón López," de la parroquia matriz del cantón La Maná, durante el año lectivo 2016- 2017 - Túmbez Cunuhay, Luis Fabián (2018)
The present research work was carried out improving the academic performance of children of the Fourth Year of Basic Education through of application of innovative strategies, according to statistical data in Ecuador show a reading habit of 19% and students that have a series of difficulties when interpreting the text; applying a traditional reading and complicate critical and creative analysis, independent reflection and teamwork. For the execution of this project we used two types of research that allowed us to have an analysis of the object of study being these exploratory and descriptive research in order to facilitated us to understand the problem and the possible solution through the search of reference data and bibliographic. The sample of the object of study was constituted by thirty boys, twenty eight girls and two teachers of the Educative Unit "Dr. Néstor Mogollón López" the survey and interview was used as a tool: a questionnaire structured by; 10 items for students and 10 ítems for teachers. In order to contribute and improve the teaching-learning process and academic performance, a manual of innovative strategies was elaborated and training workshops were given the teachers, being a skill that achieved a change of attitude in students; acceptance of the teachers and authorities of the institution, proposing our proposal as a work model to follow. This allowed having deeply motivated students, provided with critical, reflective and capable of analyzing the problems, finding solutions. Finally academic performance of the students could be experienced after the application of innovative, dynamic and practical strategies, being a form of motivation for the development of reading comprehension and student training.